2014
DOI: 10.1016/j.diii.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade gliomas: The challenges of imaging

Abstract: WHO grade II gliomas are a major challenge for magnetic resonance imaging (MRI) due to their delayed anaplastic transformation. Today it is possible to individually characterize tumor progression from diagnosis to anaplastic transformation based on the many parameters identified in studies in the literature and the possibility of integrating these data into mathematical models. Early identification of negative morphological and metabolic factors, as well as treatment follow-up, help identify predictive factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Integration of some clinico-radiological criteria with histology is commonly performed for the diagnosis of brain gliomas [20,49]. In the present study, we observed that these criteria were not helpful for IMAs.…”
Section: Discussionmentioning
confidence: 52%
“…Integration of some clinico-radiological criteria with histology is commonly performed for the diagnosis of brain gliomas [20,49]. In the present study, we observed that these criteria were not helpful for IMAs.…”
Section: Discussionmentioning
confidence: 52%
“…The limited ability for FDG‐PET/CT, even in combination with MRI, to differentiate between grade II and grade III glioma is associated with treatment and prognostication impacts . There was notable disconcordance between MRI and FDG‐PET/CT in this group.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of MRI to the disconcordance may be due to a proportion of glioma not enhancing with contrast and substantial overlap of ADCs between differing grades . The failure to enhance and overlap of ADCs may be multifactorial and influenced by the tumour microenvironment, cellularity, blood diffusion, oedema and disruption of the blood–brain barrier . These factors may also alter glucose uptake for FDG‐PET/CT where we would normally expect it to be greater in high‐grade glioma as compared to low‐grade (hypometabolic) glioma …”
Section: Discussionmentioning
confidence: 99%
“…However, after radiation, differentiation of post-treatment enhancement on MR and tumor progression for low-grade gliomas becomes challenging due to their delayed malignant transformation and potential for radiation necrosis13). Use of perfusion imaging in these low-grade tumors may detect malignant transformation with reasonable accuracy.…”
Section: Discussionmentioning
confidence: 99%